PENGUATAN KEMAMPUAN LITERASI DAN NUMERASI DALAM PRAKTIK PEMBELAJARAN BAGI PENDIDIK PAUD - Mariana Panji Ramadan; Gina Asri Ruwaida; Haniatul Hilali Nurfazriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The literacy and numeracy skills of early childhood education (PAUD) teachers are still not optimal in supporting effective and meaningful learning processes. This condition is influenced by limited understanding and lack of training in integrating literacy and numeracy into daily teaching practices. This community service program aims to enhance the literacy and numeracy competencies of PAUD educators in classroom practices. The methods employed include training, mentoring, and evaluation using a participatory approach through stages of needs analysis, planning, implementation, and evaluation. The program involved PAUD educators as the primary participants. The results indicate an improvement in participants’ understanding and skills in designing and implementing literacy and numeracy learning. In addition, participants demonstrated high enthusiasm and were able to apply the outcomes of the training in their teaching activities. Therefore, this program has a positive impact on improving the quality of learning in early childhood education.